CONTROL OF ELECTRICAL INSULATION PARAMETERS OF SINGLE-PHASE POWER TRANSFORMERS WORKING IN A UNIT WITH A GENERATOR - SHPACHUK, OLEKSANDR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The implementation of the strategy of equipment repair according to it technical condition, the aging of the main production assets of thermal and nuclear power plants, and the implementation of programs for the continuation of the operation of these energy facilities determine the urgency of issues of development and implementation of control of the technical condition of insulation of electrical equipment, as one of the key components of its effective and trouble-free operation. Modern systems for diagnosing the technical condition of electrical equipment do not realize the possibility of monitoring such electrical parameters of electrical equipment insulation as resistance and insulation capacity relative to the ground and the angle of dielectric loss, which makes it impossible to detect defects in the insulation at an early stage of their development and makes it difficult to plan the scope of repair and restoration operations on the equipment. The paper proposes a method of monitoring the technical condition of the isolation of single-phase power transformers operating in the "generator-transformer" unit, which is based on the application of an alternating current with a frequency lower than the industrial one and the control of the spreading of the alternating current with the help of current transformers built into the power transformer and insulation control circuits of high-voltage inputs. With a gradual decrease in the electrical characteristics of the controlled section of the insulation of the block transformer, the current with a frequency of 20 Hz, which flows through the insulation to the ground, increases This change in current is captured by built-in current transformers on the linear and neutral terminals of the high voltage winding, or by current transformers located at the beginning and at the end of the low voltage winding of the block transformer and through filter units and signal processing units transmits information to the control unit. The calculated values of the electrical parameters of the insulation of the block transformer, namely the insulation resistance of the equipment with respect to earth, the insulation capacity with respect to earth and the tangent of the dielectric loss angle, in combination with other methods of monitoring the technical condition, such as monitoring the concentration of gases dissolved in the transformer oil, will provide operational and repair personnel power plant with all the necessary information to make a reasoned decision regarding the possibility of further operation of the transformer. In addition, the obtained data will make it possible to detect potential problems with the insulation of the transformer and to plan in advance additional volumes of repair work and early removal of the equipment for repair without damaging it.